Excellent low-temperature NH3-SCR NO removal performance and enhanced H2O resistance by Ce addition over the Cu0.02Fe0.2CeyTi1-yOx (y = 0.1, 0.2, 0.3) catalysts. (March 2020) - Ma, Shibo; Tan, Huansheng; Li, Yushi; Wang, Peiqiang; Zhao, Chen; Niu, Xiaoyu; Zhu, Yujun
Abstract: In the present work, a serial of Cu0.02 Fe0.2 Cey Ti1-y Ox catalysts are prepared by sol-gel method and applied for NH3 -SCR of NO, meanwhile Cu0.02 Fe0.2 Ce0.2 Ti0.8 Ox shows good low-temperature NH3 -SCR performance with/without water and an outstanding water resistance. The bulk structure, redox ability, surface acidity and surface species of Cu0.02 Fe0.2 Cey Ti1-y Ox are measured and discussed by series of characterization in details to illuminate the reasons for the good low-temperature activity and water resistance. The Ce modification can tune the surface acidic distribution, improve the surface oxygen content and surface oxidation reduction cycle (Ce 4+  + Fe 2+ ↔ Ce 3+  + Fe 3+ ), which contribute the good activity. In addition, the effect of water on NH3 -SCR performance over Cu0.02 Fe0.2 TiOx and Cu0.02 Fe0·2 Ce0·2 Ti0.8 Ox are investigated emphatically by in situ DRIFTS. Graphical abstract: Image 1 Highlights: Excellent low-temperature activity for NH3 -SCR of NO over Cu0·02 Fe0·2 Ce0·2 Ti0.8 Ox . Ce addition significantly improves the water tolerance for the NH3 -SCR reaction. Enhancement of surface acidity for Cu0·02 Fe0·2 Ce0·2 Ti0.8 Ox due to the Ce addition. Increase in Lewis acid sites contributes the good water tolerance.